Effects of feeding a "Zero Land Use" diet with rumen-protected amino acids to lactating cows - Bennett, Amanda; Bradford, Barry J.; Takiya, Caio; Davidson, Melissa J. (My University, 2017)
Land use is becoming a vital concern with the everyday changes made to the environment. As human and animal populations continue to grow, more land will be needed for the cultivation of food and resources as well as the growth of industrialization. This will cause a large impact on the demand for production of forage and concentrate feeds for livestock. The cultivation of food and cash crops will generate much more crop residues and agro-industrial by-products, many of which show potential to be valuable feed resources for ruminants. The objective of this study was to evaluate a diet composed only by feedstuffs that do not affect land used for production of human food (zero land use [ZLU] combined with rumen-protected amino acids on feed intake and milk yield of mid-lactating dairy cows. Twelve multiparous Holstein cows (231±40 days in milk and 34.4±7.2 kg/d of milk yield at the start of experiment) were assigned to a 3×3 Latin square design experiment and received the following treatments: 1) Typical lactation total mixed ration (TMR, control); 2) a TMR composed of ZLU feedstuff (ZLU); and 3) ZLU with top-dressed rumen-protected amino acids [ZLU-AA; 77 g/d Aji-pro-L (Ajinomoto, Chicago, IL) and 45 g/d MetaSmart (Addiseo, Antony, France)]. ZLU diet consisted of hay from the winter intercropping of triticale and crimson clover, wheat middlings, corn gluten feed, corn hominy, spent coffee grounds, whole cottonseed with lint, molasses and a vitamin/mineral mixture. Each experimental period lasted 21 days in which the final 4 days were used for sampling. Cows were housed in a tie-stall barn and milked twice a day. Feed offered and refusals were weighed daily to determine feed intake, and milk yield was recorded in each milking during the sampling period. Data was submitted to analysis of variance and differences among treatments were determined by Fit Least Squares of JMP (Statistical Software, SAS Institute, Cary, NC) including in the model the random effects of period and cow, and fixed effects of treatment and block. Although the experiment is still running, statistical analyses were performed based on the data from the first two periods. There was a tendency (P=0.068) to ZLU diets decrease feed intake of dairy cows, where the average feed intake was 42.1, 35.6, and 38.5 kg/d for cows fed control, ZLU and ZLU-AA, respectively. ZLU diets decreased (P<0.0001), and rumen-protected amino acid addition had no effect on milk yield of cows. The average milk production of cows was 36.2, 24.3 and 25.8 kg/d for cows fed control, ZLU and ZLU-AA, respectively. In conclusion, both ZLU and ZLU-AA diets had a negative impact on productive performance of mid-lactating cows.
Keywords: Spring 2017